Kidney transcriptome response to salinity adaptation in Labeo rohita - Harshini, Vemula; Shukla, Nitin; Raval, Ishan; Kumar, Sujit; Shrivastava, Vivek; Patel, Amrutlal K.; Joshi, Chaitanya G. (Frontiers in Physiology, 2022)
The increasing salinization of the freshwater resources owing to global warming raises the concern for freshwater aquaculture. In this regard, the present study aimed at one of the most consumer demanded freshwater fish in India, Labeo rohita (rohu) adaptation to varying degrees of salinity concentrations. The RNA-seq analysis of kidney tissue samples of L. rohita maintained at 2, 4, 6 and 8 ppt salinity done and differentially expressed genes involved in various pathways were studied. A total of 755, 834, 738 and 716 transcripts were down regulated and 660, 926, 576 and 908 transcripts were up regulated in 2, 4, 6 and 8 ppt salinity treatment groups respectively with reference to the control. Significant number of candidate genes were found to illustrate the crucial role in salinity acclimatization of rohu classified into functional categories such as calcium ion regulation, osmoregulation, hypoxia regulation, osmolyte production, energy metabolism, immune response and structural reorganization. The results elucidate a step forward in understanding the osmoregulatory process in L. rohita and their adaptation to salinity changes.